Powdery composition and application thereof

By controlling the accumulation angle and loose density of the lignin derivative copolymer, the fluidity and dispersion of the hydraulic composition additives are solved, good powder fluidity and initial dispersion are achieved, and its solubility and curability in the hydraulic composition are improved.

JP2025019304AActive Publication Date: 2025-02-06NIPPON PAPER IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024207030
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-07-25
Filing Date
2024-11-28
Publication Date
2025-02-06
Estimated Expiration
2040-07-21

AI Technical Summary

Technical Problem

In the prior art, lignin derivatives as additives for hydraulic compositions do not have good dispersion when added in small amounts, and it is difficult to make a tablet, which affects its solubility and dispersion in hydraulic compositions.

Method used

The copolymer containing lignin derivatives and specific structural units is used to control its accumulation angle and loose density, ensuring that the powdered composition has a accumulation angle of 50.0° or less and a loose density of 0.4 g/cm³ or greater, and achieving good powder flowability and initial dispersion by controlling the particle size distribution and particle size.

Benefits of technology

The powder flowability similar to that of the conventional lignin derivatives is achieved, while the initial dispersion and dispersion retention in the hydraulic composition is improved, and it is easy to cure and dissolve well in the hydraulic composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019304000001
    Figure 2025019304000001
  • Figure 2025019304000002
    Figure 2025019304000002
  • Figure 2025019304000003
    Figure 2025019304000003
Patent Text Reader

Abstract

To provide a powdery composition suitable for an additive for a hydraulic composition which has powder flowability equivalent to that of a conventional additive for a powdery hydraulic composition and excellent initial dispersibility or easy solidification in which the resulting solid agent has good solubility in a hydraulic composition and also has excellent dispersibility.SOLUTION: There is provided a powdery composition which comprises at least a component (A): a lignin derivative and a component (B): a copolymer constituted by a predetermined constitutional unit and satisfies at least one selected from an angle of repose of 50.0 degrees or less, a loose bulk density of 0.40 g / cm3 or less, an angle of collapse of 27.0 degrees or more and a particle diameter distribution of 100 μm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powdery composition and uses thereof, and more particularly to a powdery composition, a solid composition, an additive for a hydraulic composition, and a hydraulic composition. [Background technology]

[0002] Lignin is a natural polymeric substance found in trees, accounting for approximately 30% of wood. Lignin is found in large amounts in waste liquor from kraft pulp production (kraft pulp waste liquor) and waste liquor from sulfite pulp production (sulfite pulp waste liquor). In recent years, lignin has been attracting attention as a biomass resource from the perspective of reducing environmental impact.

[0003] Kraft lignin contained in kraft pulp waste liquor and lignosulfonic acid contained in sulfite pulp waste liquor each have different physical properties and are used for various purposes. In addition, lignin derivatives obtained by sulfomethylating kraft lignin with sulfite and formaldehyde, lignin derivatives obtained by partially desulfonating lignosulfonic acid or a salt of lignosulfonic acid, and lignin purified products obtained by ultrafiltration are widely used as lignin-based dispersants in a wide range of industrial fields, such as dyes, cement, inorganic pigments, organic pigments, gypsum, coal-water slurries, agricultural chemicals, and ceramics.

[0004] Furthermore, with the aim of effectively utilizing lignin as a biomass resource, lignin derivatives have been proposed that can improve the dispersibility of various dispersed substances, regardless of their application, such as cement, dyes, and oil field drilling mud (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-240224 A Summary of the Invention [Problem to be solved by the invention]

[0006] The solid lignin derivative has good powder properties and is therefore easy to handle when transporting or adding the agent. On the other hand, the addition of a small amount of a lignin derivative as a conventional additive for hydraulic compositions does not provide a satisfactory dispersibility effect, and in order to achieve initial dispersibility and dispersion retention in a hydraulic composition, it is necessary to add a large amount of the lignin derivative. Therefore, there is a demand for the development of a powdery additive for hydraulic compositions that has powder properties equivalent to those of conventional solid lignin derivatives and is excellent in initial dispersibility and dispersion retention.

[0007] In recent years, tablet-type additives have started to emerge as a new product form for hydraulic composition additives. Tablet-type additives are superior in transportability and workability compared to liquid and powder products, which have been the mainstream product forms for hydraulic composition additives up to now. However, the powder characteristics of the lignin derivatives used as additives for conventional hydraulic compositions are not suitable for tableting, making tableting difficult, and even if tableting is possible, the solubility of the tablets in the hydraulic composition is poor, and the effect of dispersibility is not satisfactory. Therefore, there is a demand for the development of an additive for hydraulic compositions which can be easily tableted, has good solubility in hydraulic compositions, and is also excellent in dispersibility.

[0008] The first object of the present invention is to provide a powdery composition suitable as an additive for hydraulic compositions, which has powder characteristics equivalent to those of conventional powdery additives for hydraulic compositions such as lignin derivatives, and is excellent in initial dispersibility and dispersion retention.

[0009] A second object of the present invention is to provide a powdery composition suitable for producing a solid additive for hydraulic compositions which is easily solidified, has good solubility in hydraulic compositions, and has excellent dispersibility. [Means for solving the problem]

[0010] As a result of intensive research into the above-mentioned problems, the present inventors have discovered a method for producing a sintered cellulose ester having an angle of repose of 50.0° or less and a loose bulk density of 0.4 g / cm3, which contains at least a lignin derivative and a copolymer composed of predetermined structural units. 3 The inventors have found that a powdery composition that satisfies at least one of the following requirements can solve the above problems: a collapse angle of 27.0° or more and a particle size distribution of 100 μm or more. This has led to the completion of the present invention.

[0011] That is, the present inventors provide the following invention. [1] Component (A): lignin derivative, and Component (B): a copolymer having at least two kinds of constituent units selected from the group consisting of a constituent unit (I) derived from a monomer represented by the following general formula (1), a constituent unit (II) derived from a monomer represented by the following general formula (2), and a constituent unit (III) derived from a monomer represented by the following general formula (3), The repose angle is 50.0° or less, and the loose bulk density is 0.40 g / cm 3 A powdery composition that satisfies at least one of the following: a collapse angle of 27.0° or more; and a particle size distribution of 100 μm or more. [ka] (In the above general formula (1), R 1 ~R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; p represents an integer of 0 to 2; q represents an integer of 0 to 1. A 1 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. n represents an integer of 1 to 300. R 4 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. [ka] (In the general formula (2), R 5 ~R 7 are each independently a hydrogen atom, a methyl group, or -(CH2) rCOOM 2 represents a group, provided that -(CH2) r COOM 2 When representing a group, -COOM 1 Group or other -(CH2) r COOM 2 When an anhydride group is formed, the M 1 Or M 2 does not exist. 1 ~M 2 each independently represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group. r represents an integer of 0 to 2. [ka] (In the general formula (3), R 8 ~R 10 R each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 11 represents a hydrocarbon group having 1 to 4 carbon atoms which may contain a heteroatom; and s represents an integer of 0 to 2. [2] The composition described in [1], having a collapse angle of 30.0° or more. [3] The composition according to [1] or [2], wherein the difference angle represented by the following mathematical formula (α) is 19.0° or less. Difference angle = Angle of repose - Angle of collapse (α) [4] The angle of repose is 50.0° or less, and the loose bulk density is 0.40 g / cm 3 The composition according to any one of [1] to [3], which is: [5] The composition according to [4], wherein the weight ratio of component (A) to component (B) ((A) / (B)) is 99:1 to 51:49. [6] The composition according to any one of [1] to [3], having a collapse angle of 27.0° or more and a particle size distribution of 100 μm or more. [7] The composition according to [6], wherein the weight ratio of component (A) to component (B) ((A) / (B)) is 50:50 to 1:99. [8] A solid composition, which is a solidified product of the composition according to any one of [1] to [7]. [9] The composition according to [8], wherein the solidified product is a solidified product of the composition according to [6] or [7].

[10] An additive for a hydraulic composition, comprising the composition according to any one of [1] to [9] as an active ingredient.

[11] A hydraulic composition comprising the additive according to

[10] .

[0012] As powdered additives and their uses, the following [1-1] to [1-3] are preferred. [1-1] Contains at least components (A) and (B), has an angle of repose of 50.0° or less, and a loose bulk density of 0.40 g / cm 3 The additive for a powdery hydraulic composition is as follows: [1-2] The powdery hydraulic composition additive according to [1-1], wherein the weight ratio of component (A) to component (B) ((A) / (B)) is 99:1 to 51:49. [1-3] A hydraulic composition comprising the powdery hydraulic composition additive according to [1-1] or [1-2].

[0013] As solid additives and their uses, the following [2-1] to [2-6] are preferable. [2-1] An additive for a solid hydraulic composition, which is a powder solidified product containing at least components (A) and (B) and having a collapse angle of 27.0° or more and a particle size distribution of 100 μm or more. [2-2] The additive for a solid hydraulic composition according to [2-1], having a collapse angle of 30.0° or more. [2-3] The additive for a solid hydraulic composition according to [2-1] or [2-2], wherein the difference angle represented by the following mathematical formula (α) is 19.0° or less. Difference angle = Angle of repose - Angle of collapse (α) [2-4] The additive for a solid hydraulic composition according to any one of [2-1] to [2-3], wherein the weight ratio of component (A) to component (B) ((A) / (B)) is 50:50 to 1:99. [2-5] A tablet-molded product comprising the additive for a solid hydraulic composition according to any one of [2-1] to [2-4]. [2-6] A hydraulic composition comprising the additive for a solid hydraulic composition according to any one of [2-1] to [2-4]. Effect of the Invention

[0014] According to the present invention, it is possible to provide a powdery composition suitable as an additive for hydraulic compositions, which has powder fluidity equivalent to that of conventional powdery additives for hydraulic compositions such as lignin derivatives, and is excellent in initial dispersibility and dispersion retention.

[0015] In addition, according to the present invention, it is possible to provide a powdery composition which is easy to solidify, and the resulting solidified product has good solubility in hydraulic compositions and also has excellent dispersibility, and is suitable for producing an additive for hydraulic compositions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below based on preferred embodiments thereof. In this specification, the expression "AA to BB" means from AA to BB, and the expression "(meth)acrylic" means acrylic and / or methacrylic.

[0017] [1. Powder composition] The powdery composition of the present invention comprises component (A): a lignin derivative, and component (B): a copolymer having a predetermined structural unit, and has an angle of repose of 50.0° or less and a loose bulk density of 0.40 g / cm. 3 Hereinafter, at least one of the following conditions is satisfied: the collapse angle is 27.0° or more, and the particle size distribution is 100 μm or more.

[0018] [1-1.Physical properties] The repose angle of the powdery composition is usually 50.0° or less, and preferably 48.0° or less. If the repose angle is 50.0° or less, the powder flowability and workability can be improved. The lower limit is usually 35.0° or more, but is not particularly limited. The angle of repose is a value measured using a powder property tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) on a sample adjusted to a solid content of 95% or more.

[0019] The loose bulk density of the powder composition is usually 0.40 g / cm 3 or less, preferably 0.36 g / cm 3 The loose bulk density is 0.40 g / cm 3 When the ratio is equal to or less than this, excellent powder fluidity can be obtained. In addition, the diffusibility and initial dispersibility at the time of introducing the hydraulic composition are improved. The lower limit is usually 0.25g / cm 3 However, there is no particular limitation. The loose bulk density is a value measured on a sample whose solid content has been adjusted to 95% or more, using a powder property tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)).

[0020] The disintegration angle of the powder composition is usually 27.0° or more, preferably 30.0° or more. If the disintegration angle is 27.0° or more, the powderability is reduced, so that the composition has excellent tablet suitability. In addition, when the solidified product obtained by solidifying the powder composition is added to a hydraulic composition, excellent disintegration properties can be obtained. The upper limit of the collapse angle is usually 45.0° or less, but is not particularly limited. The collapse angle is a value measured using a powder testing device (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) on a sample whose solid content was adjusted to 95% or more.

[0021] The particle size distribution of the powder composition is usually 60 μm or more, 65 μm or more, 70 μm or more, or 100 μm or more, preferably 105 μm or more, more preferably 107 μm or more, and even more preferably 200 μm or more. When the particle size distribution is within the above range, especially 100 μm or more, the intermolecular interaction becomes strong and the cohesive force between particles is improved, so that the tablet moldability can be improved. The upper limit of the particle size distribution is usually 500 μm or less, but is not particularly limited. The particle size distribution is expressed as the molecular weight distribution obtained by measuring 3 g of a powder sample under dry conditions using a laser diffraction particle size distribution measuring device (Mastersizer 3000 (Malvern)) with the horizontal axis representing particle size (μm) and the vertical axis representing volume (%), and is the value at which the cumulative distribution is 50%.

[0022] The difference angle of the powder composition is preferably 19.0° or less. If the difference angle is 19.0° or less, the powderability is reduced, so that the composition has excellent tablet suitability. In addition, when the solidified material is added to a hydraulic composition, excellent disintegrability can be obtained. The lower limit of the difference angle is usually 5.0° or more, but is not particularly limited. The difference angle is expressed by the following formula (α). Difference angle = Angle of repose - Angle of collapse (α) The difference angle is a value obtained by measuring the difference between the angle of repose and the angle of collapse using a powder property tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) for a sample with a solid content adjusted to 95% or more.

[0023] [1-2. Component (A)] The powdery composition of the present invention contains at least component (A). Component (A) is a lignin derivative. The lignin derivative may be any compound having a lignin skeleton, and is preferably lignin sulfonic acid or a salt thereof, kraft lignin, or a combination thereof. Here, lignin sulfonic acid refers to a compound in which at least a portion of lignin or a derivative thereof is substituted with a sulfonic acid (salt) group. Kraft lignin refers to a compound in which at least a portion of lignin or a derivative thereof has a thiol group. Component (A) may be one type of lignin derivative or a combination of two or more types.

[0024] It is difficult to uniformly specify the chemical structure of a lignin derivative by a general formula or the like, because the lignin that constitutes the lignin derivative has a very complex molecular structure.

[0025] When the powdery composition of the present invention is used as an additive for a powdery hydraulic composition, the content of component (A) is preferably 51% by weight or more, more preferably 55% by weight or more, and even more preferably 60% by weight or more, based on the total amount of components (A) and (B). When the content of component (A) is 51% by weight or more, a powdery material having good powder flowability can be obtained in good yield.

[0026] When the powdery composition of the present invention is used as an additive for a solid hydraulic composition, the content of component (A) is preferably less than 50% by weight, more preferably 45% by weight or less, based on the total amount of components (A) and (B). When the content of component (A) is less than 50% by weight, a solid product having good moldability can be obtained in good yield.

[0027] The lignin derivative may be prepared or may be a commercially available product. Here, the preparation method of the lignin derivative is exemplified below. However, the lignin derivative is not limited to the one prepared by the preparation method described below.

[0028] (Method for preparing lignin derivatives) The lignin derivative can be prepared, for example, by subjecting a lignocellulosic raw material to a sulfite treatment, preferably by subjecting a lignocellulosic raw material to a sulfite cooking treatment.

[0029] The lignocellulose raw material is not particularly limited as long as it contains lignocellulose in the structure, and examples thereof include pulp raw materials such as wood and non-wood. Examples of wood include coniferous trees such as Yezo spruce, red pine, cedar, and cypress, and broad-leaved trees such as white birch and beech. The age and location of the wood are not important. Therefore, wood harvested from trees of different ages or from different locations of a tree may be used in combination. Non-wood materials include, for example, bamboo, kenaf, reed, and rice. The lignocellulosic raw material may be one of these materials, or two or more of them may be used in combination.

[0030] The sulfite treatment can be carried out by contacting at least one of sulfurous acid and a sulfite salt with a lignocellulosic raw material to obtain an intermediate product. The conditions for the sulfite treatment are not particularly limited as long as they allow introduction of a sulfonic acid (salt) group to the α-carbon atom of the side chain of lignin contained in the lignocellulosic raw material.

[0031] The sulfite treatment is preferably carried out by a sulfite cooking method, which allows more quantitative sulfonation of the lignin in the lignocellulosic raw material. The sulfite cooking method is a method in which lignocellulosic raw materials are reacted at high temperatures in a solution of at least one of sulfurous acid and a sulfite salt (e.g., an aqueous solution: cooking liquor). This method has been established and is being used industrially as a method for producing sulfite pulp. Therefore, by carrying out the sulfite treatment by the sulfite cooking method, it is possible to improve the economic efficiency and ease of implementation.

[0032] When sulfite cooking is carried out, examples of the sulfite salt include magnesium salts, calcium salts, sodium salts and ammonium salts.

[0033] The sulfurous acid (SO2) concentration in the solution of at least one of sulfurous acid and a sulfite salt is not particularly limited, but the ratio of the weight (g) of SO2 to 100 mL of the solution is preferably 1 g / 100 mL or more.

[0034] The pH value of the sulfurous acid treatment is not particularly limited, but is preferably 10 or less, and more preferably 5 or less when sulfite cooking is performed. The lower limit of the pH value is preferably 0.1 or more, and more preferably 0.5 or more when sulfite cooking is performed. The pH value during the sulfurous acid treatment is preferably 0.1 to 10, and more preferably 0.5 to 5 when sulfite cooking is performed.

[0035] The temperature of the sulfite treatment is not particularly limited, but is preferably 170° C. or lower. The lower limit is preferably 70° C. or higher.

[0036] In the sulfite treatment, it is preferable to add a compound that supplies a counter cation (salt). By adding a compound that supplies a counter cation, the pH value in the sulfite treatment can be kept constant. Examples of compounds that supply counter cations include MgO, Mg(OH)2, CaO, Ca(OH)2, CaCO3, NH3, NH4OH, NaOH, NaHCO3, and Na2CO3. The counter cation is preferably a sodium ion, a magnesium ion, or a calcium ion. The inorganic salts are usually contained in the lignin derivative in an amount of about 3 to 20%, and can be measured by a known method.

[0037] In the sulfurous acid treatment, when a solution of at least one of sulfurous acid and sulfite is used, the solution may contain, in addition to SO2, the above-mentioned counter cation (salt) and a digestion and penetration agent (e.g., a cyclic ketone compound such as anthraquinone sulfonate, anthraquinone, or tetrahydroanthraquinone), as necessary.

[0038] There is no limitation on the equipment used in the sulfite treatment, and for example, generally known dissolving pulp manufacturing equipment can be used.

[0039] The intermediate product may be separated from the solution of at least one of sulfurous acid and sulfite salt according to a conventional method, for example, a method for separating the sulfurous acid pulping wastewater after sulfurous acid pulping.

[0040] Next, the intermediate composition is washed and dehydrated to obtain a sulfite-treated product. By washing and dehydrating, components contained in the intermediate composition that cannot be completely removed by the sulfite treatment can be removed.

[0041] The washing may be carried out in the same manner as the washing of unbleached sulfite pulp obtained by the sulfite cooking method. The washing may be a single-stage washing or a multi-stage washing. By carrying out multi-stage washing, the washing can be carried out sufficiently. When carrying out multi-stage washing, dehydration may be carried out each time, or may be carried out only for some of the times. Washing is usually performed using a washing machine. The washing machine used for washing is not particularly limited. For example, a displacement washing type washing machine and a dilution dehydration washing type washing machine can be mentioned.

[0042] The dehydration can be carried out under ordinary conditions, for example, in the same manner as in the dehydration of unbleached sulfite pulp after washing obtained in the sulfite cooking method. Dehydration is usually performed using a dehydrator. The type of dehydrator used for dehydration is not particularly limited. Examples of the dehydrator include a drum-type squeezer dehydrator, a rotary press, and a continuous squeezer dehydrator.

[0043] Thereafter, the sulfite-treated product is washed and dehydrated as necessary, and then separated and purified to obtain the desired lignin derivative. Examples of the separation and purification include an alkaline oxidation treatment step and an ultrafiltration treatment step.

[0044] When the alkaline oxidation treatment is carried out, after the sulfite-treated product is subjected to the alkaline oxidation treatment, insoluble matters can be centrifuged and recovered as a supernatant.

[0045] The alkaline oxidation treatment can be carried out by placing the sulfurous acid-treated product under alkaline conditions. Placing under alkaline conditions usually means placing the product in an aqueous solution having a pH value of 8 or more, preferably a pH value of 9 or more. The upper limit of the pH value is usually 14.

[0046] In the alkaline oxidation treatment, an alkaline substance is usually brought into contact with the sulfite treatment product. The alkaline substance is not particularly limited, but examples thereof include calcium hydroxide, magnesium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia. Among these, sodium hydroxide is preferred. The alkaline substances may be used alone or in combination of two or more.

[0047] Examples of a method for contacting an alkaline substance with the sulfurous acid treated product include a method of preparing a dispersion or solution (e.g., an aqueous dispersion or aqueous solution) of the sulfurous acid treated product and adding an alkaline substance to the dispersion or solution, and a method of adding a solution or dispersion (e.g., an aqueous dispersion or aqueous solution) of the alkaline substance to the sulfurous acid treated product.

[0048] The temperature of the alkaline oxidation treatment is not particularly limited, but is preferably 40° C. or higher, more preferably 60° C. or higher, and the upper limit is preferably 150° C. or lower.

[0049] The amount of the alkaline substance in the alkaline oxidation treatment is preferably 0.5 to 20% by weight, more preferably 1.0 to 15% by weight, based on the solids weight of the sulfurous acid treated product, or, when an aqueous solution or dispersion is prepared by dispersing the alkali-treated extract in an aqueous solvent (e.g., water), based on the weight of the aqueous solution or dispersion.

[0050] The time for the alkaline oxidation treatment is not particularly limited, but is preferably 0.1 hours or more, more preferably 0.5 hours or more, and is preferably 10 hours or less, more preferably 6 hours or less.

[0051] Prior to the alkaline oxidation treatment, the sulfite treatment product may be dissolved, dispersed, or the concentration adjusted (preparation of a solution or dispersion in an aqueous solvent such as water) as necessary. Dispersion treatment can be performed by passing through a disc refiner, adding to a mixer or disperser, kneading, etc. The concentration can be adjusted, for example, by using an aqueous solvent such as water.

[0052] The ultrafiltration process can be carried out using an ultrafiltration membrane (hereinafter also referred to as "UF membrane"). As the UF membrane, a known UF membrane can be used. For example, a hollow fiber membrane, a spiral membrane, a tubular membrane, and a flat membrane can be mentioned. The material of the UF membrane may be any known material. For example, cellulose acetate, aromatic polyamide, polyvinyl alcohol, polysulfone, polyvinylidene fluoride, polyethylene, polyacrylonitrile, and ceramic may be used. The UF membrane may be a commercially available product.

[0053] The molecular weight cutoff of the UF membrane is preferably 5,000 to 30,000, more preferably 10,000 to 25,000, and even more preferably 15,000 to 23,000. When a UF membrane with a molecular weight cutoff of 5,000 or more is used, it is possible to prevent the separation speed of the black liquor from being excessively slowed. In addition, when a UF membrane with a molecular weight cutoff of 30,000 or less is used, it is possible to prevent lignin from being unable to be separated from the black liquor.

[0054] The concentration rate by ultrafiltration using a UF membrane can be set arbitrarily. That is, the ultrafiltration can be stopped when the amount of the concentrate flowing out reaches a desired amount.

[0055] The temperature of the black liquor during ultrafiltration is not particularly limited, and is preferably 20 to 80°C, and more preferably 20 to 70°C in consideration of the heat resistance of the UF membrane material. The pH value of the black liquor during the ultrafiltration treatment is preferably 2 to 11. The solids concentration (w / w) of the black liquor during ultrafiltration is preferably from 2 to 30%, more preferably from 5 to 15%.

[0056] [1-3. Ingredient (B)] The powdery composition of the present invention contains at least component (B). Component (B) is a copolymer having at least two types of structural units selected from the group consisting of structural unit (I) derived from a monomer represented by general formula (1), structural unit (II) derived from a monomer represented by general formula (2), and structural unit (III) derived from a monomer represented by general formula (3). The copolymer of component (B) may be one type or a combination of two or more types.

[0057] When the powdery composition of the present invention is used as an additive for a powdery hydraulic composition, the content of component (B) is preferably 1 to 49% by weight, more preferably 1 to 45% by weight, and even more preferably 1 to 40% by weight, based on the total amount of components (A) and (B). When the content of component (B) is within this range, a powdery material having better water solubility after drying can be obtained.

[0058] When the powdery composition of the present invention is used as a raw material for an additive for a solid hydraulic composition, the content of component (B) is preferably 50 to 90% by weight, more preferably 55 to 90% by weight, based on the total amount of components (A) and (B). When the content of component (B) is within this range, a solid product having better water solubility after drying can be obtained. Details of each constituent unit are given below.

[0059] (Structural unit (I)) The structural unit (I) is a structural unit derived from a monomer represented by the following general formula (1).

[0060] [ka]

[0061] In general formula (1), R 1 ~R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; p represents an integer of 0 to 2; q represents an integer of 0 to 1. A 1 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. n represents an integer of 1 to 300. R 4 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. R 1 is preferably a hydrogen atom. 2 R is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a methyl group. 3 is preferably a hydrogen atom.

[0062] In general formula (1), A 1O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. Examples of the oxyalkylene group (alkylene glycol unit) include an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit). Among these, an oxyethylene group and an oxypropylene group are preferred.

[0063] The above-mentioned "may be the same or different" means that A 1 If multiple Os are included (n is 2 or more), each A 1 This means that O may be the same oxyalkylene group or different (two or more types) oxyalkylene groups. 1 In the case where a plurality of O's are contained, there may be mentioned an embodiment in which two or more oxyalkylene groups selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group are mixed. More specifically, an embodiment in which an oxyethylene group and an oxypropylene group are mixed, or an embodiment in which an oxyethylene group and an oxybutylene group are mixed, is preferable, and an embodiment in which an oxyethylene group and an oxypropylene group are mixed is more preferable. In an embodiment in which different oxyalkylene groups are mixed, the addition of two or more types of oxyalkylene groups may be in a block form or a random form.

[0064] In the general formula (1), n ​​is the average number of moles of oxyalkylene groups added, and represents an integer of 1 to 300. n is preferably 1 to 200. The average number of moles added means the average value of the number of moles of oxyalkylene groups added to 1 mole of a monomer.

[0065] In general formula (1), R 4 R represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. 4 R is preferably a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and further preferably a hydrogen atom or a methyl group. 4If the number of carbon atoms is within this range, the number of carbon atoms will not be too large, and therefore when used as an additive for a hydraulic composition, good dispersibility is exhibited.

[0066] Examples of the method for producing the monomer represented by the general formula (1) include a method of adding 1 to 300 moles of alkylene oxide to an unsaturated alcohol such as allyl alcohol, methallyl alcohol, or 3-methyl-3-buten-1-ol. Examples of monomers that can be produced by this method include (poly)ethylene glycol allyl ether, (poly)ethylene glycol methallyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, (poly)ethylene glycol (poly)propylene glycol allyl ether, (poly)ethylene glycol (poly)propylene glycol methallyl ether, (poly)ethylene (poly)propylene glycol allyl ether, (poly)ethylene (poly)propylene glycol methallyl ether, (poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, (poly)ethylene (poly)butylene glycol allyl ether, (poly)ethylene (poly)butylene glycol methallyl ether, (poly)ethylene (poly) butylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene glycol allyl ether, methoxy(poly)ethylene glycol methallyl ether, methoxy(poly)ethylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)propylene glycol allyl ether, methoxy(poly)ethylene (poly)propylene glycol methallyl ether, methoxy(poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)butylene glycol allyl ether, methoxy(poly)ethylene (poly)butylene glycol methallyl ether, and methoxy(poly)ethylene (poly)butylene glycol 3-methyl-3-butenyl ether. Among these, from the viewpoint of the balance between hydrophilicity and hydrophobicity, (poly)ethylene glycol (meth)allyl ether, (poly)ethylene glycol (poly)propylene glycol (meth)allyl ether, (poly)ethylene (poly)propylene glycol (meth)allyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, and (poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether are preferred.

[0067] Another example of a method for producing the monomer represented by general formula (1) is the esterification of an unsaturated monocarboxylic acid such as (meth)acrylic acid with a (poly)alkylene glycol such as (poly)ethylene glycol, (poly)ethylene (poly)propylene glycol, (poly)ethylene (poly)butylene glycol, methoxy(poly)ethylene glycol, methoxy(poly)ethylene (poly)propylene glycol, or methoxy(poly)ethylene (poly)butylene glycol. Examples of monomers that can be produced by this method include (poly)alkylene glycol (meth)acrylates such as (poly)ethylene glycol (meth)acrylate, (poly)ethylene (poly)propylene glycol (meth)acrylate, (poly)ethylene (poly)butylene glycol (meth)acrylate, etc.; and methoxy(poly)alkylene glycol (meth)acrylates such as (poly)alkylene glycol (meth)acrylates such as methoxy(poly)ethylene glycol (meth)acrylate, methoxy(poly)ethylene (poly)propylene glycol (meth)acrylate, methoxy(poly)ethylene (poly)butylene glycol (meth)acrylate, etc. Among these, (poly)alkylene glycol (meth)acrylate and methoxy(poly)ethylene glycol (meth)acrylate are preferred, and methoxy(poly)ethylene glycol (meth)acrylate is more preferred.

[0068] When the copolymer has the structural unit (I), it may have only one type of structural unit (I), or may have two or more types of structural units (I) derived from different monomers.

[0069] (Structural unit (II)) The structural unit (II) is a structural unit derived from a monomer represented by the following general formula (2).

[0070] [ka]

[0071] In general formula (2), R 5 ~R 7 are each independently a hydrogen atom, a methyl group, or -(CH2) r COOM 2 represents a group, provided that -(CH2) r COOM 2 When representing a group, -COOM 1 Group or other -(CH2) r COOM 2 When an anhydride group is formed, the M 1 Or M 2 does not exist. 1 ~M 2 each independently represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group, and r represents an integer of 0 to 2. R 5 is preferably a hydrogen atom. 6 is a hydrogen atom, a methyl group or (CH2) r COOM 2 is preferred. 7 is preferably a hydrogen atom.

[0072] M 1 and M 2 are the same or different and are a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group. 1 , M 2 are each preferably a hydrogen atom, an alkali metal, or an alkaline earth metal.

[0073] r represents an integer of 0 to 2. r is preferably 0 or 1, and more preferably 0.

[0074] Examples of the monomer represented by the general formula (2) include unsaturated monocarboxylic acid monomers and unsaturated dicarboxylic acid monomers. Specific examples of the unsaturated monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and the like, and their monovalent metal salts, ammonium salts, and organic amine salts. Specific examples of the unsaturated dicarboxylic acid include maleic acid, itaconic acid, citraconic acid, fumaric acid, and the like, and their monovalent metal salts, ammonium salts, and organic amine salts, or their anhydrides. Preferred examples of the monomer represented by the general formula (2) include acrylic acid, methacrylic acid, and maleic acid.

[0075] When the copolymer has the structural unit (II), it may have only one type of structural unit (II), or may have two or more types of structural units (II) derived from different monomers.

[0076] (Structural unit (III)) The structural unit (III) is a structural unit derived from a monomer represented by the following general formula (3).

[0077] [ka]

[0078] In general formula (3), R 8 ~R 10 R each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 11 represents a hydrocarbon group having 1 to 4 carbon atoms which may contain a heteroatom; s represents an integer of 0 to 2. Examples of alkyl groups having 1 to 3 carbon atoms include R 1 ~R 3 Similar to the example in R 8 is preferably a hydrogen atom. 9 is preferably a hydrogen atom. 10 is preferably a hydrogen atom.

[0079] In general formula (3), R 11 represents a hydrocarbon group having 1 to 4 carbon atoms which may contain a heteroatom. The number of carbon atoms is preferably 1 to 3, more preferably 2 to 3, and even more preferably 3. Examples of the heteroatom include an oxygen atom, a nitrogen atom, a phosphorus atom, and a silicon atom. Among these, an oxygen atom is preferred. Examples of the hydrocarbon group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a butyl group, an isobutyl group, and a sec-butyl group. R 11 The number of heteroatoms contained in may be 1 or may be 2 or more. When two or more heteroatoms are contained, each heteroatom may be the same or different from each other.

[0080] R 11 is preferably a hydrocarbon group containing a heteroatom and having 1 to 4 carbon atoms, more preferably a hydrocarbon group containing an oxygen atom and having 1 to 4 carbon atoms. Examples of such groups include a 2-hydroxyethyl group, a 2-hydroxypropyl group, a 4-hydroxybutyl group, and a glyceryl group. Among these, a 2-hydroxyethyl group and a 2-hydroxypropyl group are preferred.

[0081] In formula (3), s represents an integer of 0 to 2. s is preferably 0.

[0082] The monomer represented by the general formula (3) may be, for example, a monoester of an unsaturated monocarboxylic acid. Examples of the unsaturated monocarboxylic acid monoester include methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glyceryl (meth)acrylate. Among these, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate are preferred.

[0083] When the copolymer has the structural unit (III), it may have only one type of structural unit (III), or may have two or more types of structural units (III) derived from different monomers.

[0084] When the copolymer has at least two structural units selected from the group consisting of the structural units (I) to (III), compatibility with component (A) is improved, and component (A) can be more uniformly dispersed in the cement composition.

[0085] The copolymer may contain a structural unit (IV) in addition to the structural units (I) to (III).

[0086] (Structural unit (IV)) The structural unit (IV) is a structural unit derived from a monomer copolymerizable with the monomers represented by the above general formulas (1) to (3). The monomers copolymerizable with the monomers represented by the above general formulas (1) to (3) are structurally distinct from the monomers represented by the above general formulas (1) to (3). The monomers constituting the structural unit (IV) are not particularly limited, and examples thereof include the following monomers. These monomers can be used alone or in combination of two or more.

[0087] A monomer represented by general formula (IV-1):

[0088] [ka]

[0089] Examples of the monomer represented by the general formula (IV-1) include 3- and 3'-allyl-substituted bisphenols such as 4,4'-dihydroxydiphenylpropane, 4,4'-dihydroxydiphenylmethane, and 4,4'-dihydroxydiphenylsulfone.

[0090] A monomer represented by general formula (IV-2):

[0091] [ka]

[0092] Examples of the monomer represented by the above general formula (IV-2) include 3-allyl-substituted bisphenols such as 4,4'-dihydroxydiphenylpropane, 4,4'-dihydroxydiphenylmethane, and 4,4'-dihydroxydiphenylsulfone.

[0093] A monomer represented by general formula (IV-3):

[0094] [ka]

[0095] An example of the monomer represented by the general formula (IV-3) is allylphenol.

[0096] Half esters and diesters of unsaturated dicarboxylic acids, such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, and citraconic acid, with alcohols having 1 to 30 carbon atoms;

[0097] Half amides and diamides of the above unsaturated dicarboxylic acids with amines having 1 to 30 carbon atoms;

[0098] half esters, half amides, diesters and diamides of (poly)oxyalkylene alkyl ethers or (poly)oxyalkylene alkyl amines obtained by adding 1 to 500 moles of alkylene oxide having 2 to 18 carbon atoms to the above alcohols or amines, and the above unsaturated dicarboxylic acids;

[0099] Half esters and diesters of the above unsaturated dicarboxylic acids with glycols having 2 to 18 carbon atoms or polyalkylene glycols having 2 to 500 moles of such glycols added;

[0100] Half amides of maleamic acid and glycols having 2 to 18 carbon atoms or polyalkylene glycols having 2 to 500 moles of such glycols added;

[0101] (poly)ethylene glycol mono(meth)acrylate, (poly)propylene glycol mono(meth)acrylate, (poly)butylene glycol mono(meth)acrylate, and the like, in which 1 to 500 moles of alkylene oxide having 2 to 18 carbon atoms are added to unsaturated monocarboxylic acids such as (meth)acrylic acid (however, excluding monomers represented by general formulas (1) to (3));

[0102] (poly)alkylene glycol di(meth)acrylates such as triethylene glycol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and (poly)ethylene glycol (poly)propylene glycol di(meth)acrylate;

[0103] Polyfunctional (meth)acrylates such as hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and trimethylolpropane di(meth)acrylate;

[0104] (Poly)alkylene glycol dimaleates such as triethylene glycol dimaleate and polyethylene glycol dimaleate;

[0105] unsaturated sulfonic acids such as vinyl sulfonate, (meth)allyl sulfonate, 2-(meth)acryloxyethyl sulfonate, 3-(meth)acryloxypropyl sulfonate, 3-(meth)acryloxy-2-hydroxypropyl sulfonate, 3-(meth)acryloxy-2-hydroxypropyl sulfophenyl ether, 3-(meth)acryloxy-2-hydroxypropyloxysulfobenzoate, 4-(meth)acryloxybutyl sulfonate, (meth)acrylamidomethyl sulfonic acid, (meth)acrylamidoethyl sulfonic acid, 2-methylpropanesulfonic acid (meth)acrylamide, and styrenesulfonic acid, as well as their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts;

[0106] Amides of unsaturated monocarboxylic acids and amines having 1 to 30 carbon atoms, such as methyl (meth)acrylamide;

[0107] vinyl aromatics such as styrene, α-methylstyrene, vinyltoluene, and p-methylstyrene;

[0108] Alkanediol mono(meth)acrylates such as 1,5-pentanediol mono(meth)acrylate and 1,6-hexanediol mono(meth)acrylate (excluding monomers represented by general formula (3));

[0109] Dienes such as butadiene, isoprene, 2-methyl-1,3-butadiene, and 2-chloro-1,3-butadiene;

[0110] Unsaturated amides such as (meth)acrylamide, (meth)acrylalkylamide, N-methylol (meth)acrylamide, and N,N-dimethyl (meth)acrylamide;

[0111] Unsaturated cyanides such as (meth)acrylonitrile and α-chloroacrylonitrile;

[0112] Unsaturated esters such as vinyl acetate and vinyl propionate;

[0113] Unsaturated amines such as aminoethyl (meth)acrylate, methylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, dibutylaminoethyl (meth)acrylate, and vinylpyridine (excluding monomers represented by general formula (3));

[0114] Divinyl aromatics such as divinylbenzene; cyanurates such as triallyl cyanurate;

[0115] Allyls such as (meth)allyl alcohol and glycidyl (meth)allyl ether;

[0116] Vinyl ethers or allyl ethers such as methoxypolyethylene glycol monovinyl ether, polyethylene glycol monovinyl ether, methoxypolyethylene glycol mono(meth)allyl ether, and polyethylene glycol mono(meth)allyl ether (excluding the monomer represented by the general formula (1));

[0117] Siloxane derivatives such as polydimethylsiloxane propylaminomaleamic acid, polydimethylsiloxane aminopropylene aminomaleamic acid, polydimethylsiloxane bis-(propylaminomaleamic acid), polydimethylsiloxane bis-(dipropyleneaminomaleamic acid), polydimethylsiloxane-(1-propyl-3-acrylate), polydimethylsiloxane-(1-propyl-3-methacrylate), polydimethylsiloxane bis-(1-propyl-3-acrylate), and polydimethylsiloxane bis-(1-propyl-3-methacrylate) (however, excluding the monomer represented by general formula (3)).

[0118] The copolymer may have only one type of structural unit (IV), or may have two or more types of structural units (IV) derived from mutually different monomers.

[0119] In the copolymer, each of the structural units (I) to (IV) may be a structural unit composed of one type of monomer, or may be a structural unit composed of a combination of two or more types of monomers. Among these, the copolymer is preferably a copolymer which is a combination of the structural unit (I) and the structural unit (II), or a copolymer which is a combination of the structural units (I) to (III).

[0120] (Method of Preparing Copolymer) The copolymer can be prepared by copolymerizing the respective predetermined monomers by a known method, such as polymerization in a solvent or bulk polymerization.

[0121] Examples of the solvent used in the polymerization in a solvent include water, lower alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., aliphatic hydrocarbons such as cyclohexane, n-hexane, etc., esters such as ethyl acetate, etc., ketones such as acetone, methyl ethyl ketone, etc. From the viewpoint of the solubility of the raw material monomers and the resulting copolymer, it is preferable to use at least one of water and lower alcohols, and it is more preferable to use water.

[0122] When the polymerization reaction is carried out in a solvent, each monomer and the polymerization initiator may be continuously dropped into a reaction vessel, or a mixture of each monomer and the polymerization initiator may be continuously dropped into a reaction vessel. Alternatively, a solvent may be charged into a reaction vessel, and a mixture of the monomers and the solvent and a polymerization initiator solution may be continuously dropped into the reaction vessel, or a part or all of the monomers may be charged into the reaction vessel, and the polymerization initiator may be continuously dropped into the reaction vessel.

[0123] The polymerization initiator that can be used in the polymerization reaction is not particularly limited. Examples of polymerization initiators that can be used when performing a polymerization reaction in an aqueous solvent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate; water-soluble peroxides such as t-butyl hydroperoxide and hydrogen peroxide. In this case, accelerators such as L-ascorbic acid, sodium hydrogen sulfite, and Mohr's salt may be used in combination. Examples of polymerization initiators that can be used when performing a polymerization reaction in an organic solvent such as a lower alcohol, an aromatic hydrocarbon, an aliphatic hydrocarbon, an ester, or a ketone include peroxides such as benzoyl peroxide and lauryl peroxide; hydroperoxides such as cumene peroxide; and azo compounds such as azobisisobutyronitrile. In this case, accelerators such as amine compounds may be used in combination. The polymerization initiator that can be used when performing a polymerization reaction in a water-lower alcohol mixed solvent may be appropriately selected from the above-mentioned polymerization initiators or combinations of polymerization initiators and accelerators. The polymerization temperature varies depending on polymerization conditions such as the type of solvent and polymerization initiator used, but is usually 40 to 120°C.

[0124] In the polymerization reaction, the molecular weight can be adjusted by using a chain transfer agent as necessary. Examples of the chain transfer agent include known thiol compounds such as mercaptoethanol, thioglycerol, thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, octyl thioglycolate, and 2-mercaptoethanesulfonic acid; phosphorous acid, hypophosphorous acid, or salts thereof (sodium hypophosphite, potassium hypophosphite, etc.), sulfurous acid, hydrogen sulfite, dithionous acid, metabisulfite, or salts thereof (sodium sulfite, potassium sulfite, sodium hydrogen sulfite, potassium hydrogen sulfite, sodium dithionite, potassium dithionite, sodium metabisulfite, potassium metabisulfite, etc.), lower oxides or salts thereof. These chain transfer agents may be used alone or in combination of two or more.

[0125] When a polymerization reaction is carried out in an aqueous solvent to obtain a copolymer, the pH during the polymerization reaction is usually strongly acidic due to the influence of a monomer having an unsaturated bond. However, this may be adjusted to an appropriate pH. If it is necessary to adjust the pH during the polymerization reaction, the pH may be adjusted using an acidic substance such as phosphoric acid, sulfuric acid, nitric acid, alkyl phosphoric acid, alkyl sulfuric acid, alkyl sulfonic acid, or (alkyl)benzenesulfonic acid. Among these acidic substances, it is preferable to use phosphoric acid because of its pH buffering effect. However, it is preferable to carry out the polymerization reaction at a pH of 2 to 7 in order to eliminate the instability of the ester bond of the ester monomer. In addition, there is no particular limitation on the alkaline substance that can be used to adjust the pH, and alkaline substances such as NaOH and Ca(OH)2 are generally used. The pH adjustment may be carried out on the monomer before the polymerization reaction, or on the copolymer solution after the polymerization reaction. In addition, a part of the alkaline substance may be added before the polymerization reaction to carry out polymerization, and then the pH of the copolymer may be further adjusted (for example, adjusted to a pH of 3 to 7).

[0126] The copolymer can be prepared as a liquid. Examples of liquid solvents include aqueous solvents. Examples of aqueous solvents include water, alcohols having 1 to 6 carbon atoms (ethyl alcohol, methyl alcohol, ethylene glycol, diethylene glycol, etc.), and ketones having 1 to 6 carbon atoms (methyl isobutyl ketone, acetone, etc.). These aqueous solvents may be used alone or in combination of two or more. Water is preferred as the aqueous solvent. The lower limit of the solid content concentration in the copolymer is preferably 5% by weight or more, more preferably 15% by weight or more, and the upper limit is preferably 70% by weight or less, more preferably 65% ​​by weight or less.

[0127] Component (B) may contain at least one monomer selected from the group consisting of the above general formulas (1) to (3), which is a raw material for the copolymer. When obtaining the copolymer, treatments such as removal of the reaction solvent, concentration, purification, etc. may be carried out as necessary. These treatment methods may be conventionally known methods.

[0128] The lower limit of the weight average molecular weight (Mw) of the copolymer is preferably 5000 or more, more preferably 7000 or more, and even more preferably 10000 or more. By using a copolymer having this weight average molecular weight as component (B), the dispersibility of the cement composition can be fully exhibited when it is used as a cement composition dispersant. Therefore, the fluidity or workability can be improved. The upper limit of the weight average molecular weight is preferably 60000 or less, more preferably 45000 or less, and even more preferably 30000 or less. By using a copolymer having this weight average molecular weight as component (B), the aggregation action of particles in the cement composition can be suppressed, and the workability can be improved. The weight average molecular weight is preferably 5000 to 60000, more preferably 7000 to 45000, and even more preferably 10000 to 30000.

[0129] The lower limit of the molecular weight distribution (Mw / Mn) of the copolymer is preferably 1.0 or more, more preferably 1.2 or more. The upper limit is preferably 3.0 or less, more preferably 2.5 or less. The molecular weight distribution is preferably in the range of 1.0 to 3.0, more preferably 1.2 to 3.0, and even more preferably 1.2 to 2.5.

[0130] The weight average molecular weight can be measured by a known method using gel permeation chromatography (GPC) in terms of polyethylene glycol. The measurement conditions for GPC are not particularly limited, and the following conditions can be mentioned, for example. The weight average molecular weight in the examples described later is a value measured under these conditions. Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh or GL Science) Detector: Differential refractometer (Tosoh Corporation) Calibration curve; Polyethylene glycol standard

[0131] When the powdery composition of the present invention is used as an additive for a powdery hydraulic composition, the weight ratio of component (A) to component (B) ((A) / (B)) is preferably 99:1 to 51:49, more preferably 90:10 to 55:45, and even more preferably 80:20 to 60:40. When the weight ratio of component (A) to component (B) ((A) / (B)) satisfies the above range, sufficient initial dispersibility can be exhibited while maintaining good powderability.

[0132] When the powdery composition of the present invention is used as an additive for a solid hydraulic composition, the weight ratio of component (A) to component (B) ((A) / (B)) is preferably 1:99 to 50:50, more preferably 10:90 to 45:55, and even more preferably 20:80 to 40:60. When the weight ratio of component (A) to component (B) ((A) / (B)) satisfies the above range, sufficient water solubility and initial dispersibility can be exhibited while maintaining good tablet moldability.

[0133] [1-3. Other ingredients] The powdery composition of the present invention may contain optional components other than the above-mentioned components (A) and (B) as long as the effects of the present invention are not impaired. When the powdery composition is used as an additive for hydraulic compositions, examples of the optional components include known additives for hydraulic compositions, excipients, and lubricants such as water-soluble polymers, hardening accelerators, thickeners, polymer emulsions, air entraining agents, cement wetting agents, expansion agents, waterproofing agents, flocculants, drying shrinkage reducing agents, strength enhancing agents, antifoaming agents, AE agents, and surfactants. These may be used alone or in combination of two or more.

[0134] The water-soluble polymer may be polyalkylene glycol. More specifically, examples include polyethylene glycol, polypropylene glycol, polyethylene polypropylene glycol, polyethylene polybutylene glycol, etc. The content of the water-soluble polymer is preferably 0.01 to 50% by weight based on the component (A).

[0135] Examples of the hardening accelerator include soluble calcium salts such as calcium chloride, calcium nitrite, and calcium nitrate; chlorides such as iron chloride and magnesium chloride; thiosulfates; formic acid; and formates such as calcium formate. The hardening accelerator may be used alone or in combination of two or more. The content of the hardening accelerator is preferably 0.01 to 50% by weight based on the component (A).

[0136] [2. Solid composition] The solid composition of the present invention is a solidified product of the above-mentioned powder composition. In this specification, the solidified product refers to a processed product obtained by solidification treatment. The solidification treatment includes, for example, drying solidification treatment, granulation treatment (tabletting, extrusion), and various molding treatments, but is not particularly limited. The dosage form of the solid composition includes, for example, tablets and pellets.

[0137] [3. Additives for hydraulic compositions] The additive for hydraulic compositions of the present invention contains at least one selected from the above-mentioned powdery composition and solid composition as an active ingredient. The dosage form of the additive is preferably a powder or solid (e.g., tablet, pellet). When the dosage form of the additive is powdery, it is preferable that the active ingredient is a powdery composition whose angle of repose and loose bulk density satisfy the above conditions. When the dosage form of the additive is solid, it is preferable that the active ingredient is a solidified powdery composition whose collapse angle and particle size distribution satisfy the above conditions, and it is more preferable that the active ingredient is a solidified powdery composition whose collapse angle and / or difference angle satisfy the above conditions.

[0138] In this specification, the powdered additive for hydraulic composition means an additive for hydraulic composition which has been subjected to drying and solidifying treatment but not granulation treatment in the manufacturing process, and the solid additive for hydraulic composition means an additive for hydraulic composition which has been subjected to solidifying treatment such as drying and solidifying treatment and granulation treatment in the manufacturing process.

[0139] The water content of the additive for hydraulic compositions is usually 50% by weight or less, preferably 30% by weight or less, and more preferably 10% by weight or less. The water content of the additive for hydraulic compositions can be measured using an infrared moisture meter (manufactured by Kett Electric Laboratory Co., Ltd.). The solid content (%) in the examples below was measured using this device.

[0140] The additive for hydraulic composition may contain components other than the powder composition and the solid composition. For example, other additives for hydraulic composition may include the agents exemplified in 1-3 above.

[0141] [4. Method for producing powder composition] The present invention provides a method for converting a liquid material containing at least component (A) and component (B) into a dry powder. The details of each component are the same as those described in [1. Powder composition].

[0142] The drying method may be a known method. For example, the method may include a method of neutralizing the polyvalent metal salt with a hydroxide of a divalent metal such as calcium or magnesium and then drying the salt; a method of supporting the polyvalent metal salt on an inorganic powder such as silica-based fine powder and drying the polyvalent metal salt; a method of drying and solidifying the polyvalent metal salt into a thin film on a support of a drying device (e.g., a drum-type drying device, a disk-type drying device, or a belt-type drying device); and a method of drying and solidifying the polyvalent metal salt using a spray dryer. The moisture content after the drying and solidifying process is usually 50% by weight or more, preferably 30% by weight or less, and more preferably 10% by weight or less. The powdered composition obtained after drying and powdering can be used as it is as an additive for a powdered hydraulic composition, or can be further subjected to a solidification treatment to obtain a solidified product, which can be used as an additive for a solid hydraulic composition. Examples of the solidification treatment include, but are not limited to, a drying and solidification treatment, a granulation treatment (tabletting, extrusion), and various molding treatments.

[0143] [5. Hydraulic composition] The hydraulic composition of the present invention contains the additive for hydraulic compositions described above in 4. More specifically, the hydraulic composition is a cement paste, mortar, concrete, plaster, etc., prepared by adding the additive for hydraulic compositions to a hydraulic material such as cement.

[0144] Examples of hydraulic materials include cement, gypsum (such as hemihydrate and dihydrate gypsum), and dolomite. The most common hydraulic material is cement.

[0145] There are no particular limitations on the cement. For example, Portland cement (normal, early strength, super early strength, moderate heat, sulfate resistance, and each low alkali type), various mixed cements (blast furnace cement, silica cement, fly ash cement), white Portland cement, alumina cement, super rapid hardening cement (1 clinker rapid hardening cement, 2 clinker rapid hardening cement, magnesium phosphate cement), cement for grouting, oil well cement, low heat cement (low heat type blast furnace cement, low heat type blast furnace cement mixed with fly ash, high belite content cement), ultra high strength cement, cement-based solidification material, ecocement (cement manufactured using one or more of urban waste incineration ash and sewage sludge incineration ash as raw materials), etc. may be added to the cement. Fine powders such as blast furnace slag, fly ash, cinder ash, clinker ash, husk ash, silica fume, silica sand powder, limestone powder, etc., gypsum, etc. may be added.

[0146] The hydraulic composition may also contain aggregate. The aggregate may be either fine aggregate or coarse aggregate. Examples of the aggregate include sand, gravel, crushed stone, granulated slag, recycled aggregate, and refractory aggregates such as silica stone, silica sand powder, clay, zircon, high alumina, silicon carbide, graphite, chrome, chromium-magnesium, and magnesia.

[0147] There is no particular limitation on the amount of additive for hydraulic compositions added to a hydraulic composition. For example, when the hydraulic composition is mortar or concrete, the following amount of additive can uniformly disperse the additive for hydraulic compositions in the cement matrix, suppress thickening of fresh concrete, and prepare a cement composition with good fluidity. The amount of additive is a ratio to the total weight of the hydraulic material (cement).

[0148] The lower limit of the amount of additive for hydraulic composition (addition amount of solid content) is preferably 0.001% by weight or more, more preferably 0.01% by weight or more, and even more preferably 0.1% by weight or more. The upper limit is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less. That is, it is preferably 0.001 to 30% by weight, more preferably 0.01 to 25% by weight, and even more preferably 0.1 to 20% by weight.

[0149] The above hydraulic composition is useful as concrete, for example, ready-mixed concrete, concrete for secondary concrete products (precast concrete), concrete for centrifugal molding, concrete for vibration compaction, steam cured concrete, lightweight aerated concrete, autoclaved lightweight aerated concrete, shotcrete, and the like. It is also effective as a mortar or concrete that requires high fluidity, such as medium fluidity concrete (concrete with a slump value in the range of 22 to 25 cm), high fluidity concrete (concrete with a slump value of 25 cm or more and a slump flow value in the range of 50 to 70 cm), self-compacting concrete, and self-leveling material. EXAMPLES

[0150] The present invention will be described in detail below with reference to examples. The following examples are provided to suitably explain the present invention, and are not intended to limit the present invention. The methods for measuring physical properties and the like are the same as those described above unless otherwise specified. Furthermore, "parts" refers to parts by weight unless otherwise specified.

[0151] [Angle of repose (°)]: Measured using a powder tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) with the angle measurement method set to "Peak Operation" using a sieve with a mesh size of 710 μm and a wire diameter of 450 μm, and used as an index of fluidity. If the angle of repose is 50.0° or less, the powder has excellent fluidity and improves workability.

[0152] [Loose bulk density (g / cm 3 )]: Measured using a powder tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) with a sieve with a mesh size of 710 μm and a wire diameter of 450 μm. The loose bulk density was 0.40 g / cm 3 If it exceeds this value, the diffusibility after the hydraulic composition is introduced deteriorates, and the initial dispersibility deteriorates.

[0153] [Collapse angle (°)]: Measured using a powder tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)) with the angle measurement method set to "Peak Operation" using a sieve with a mesh size of 710 μm and a wire diameter of 450 μm. A collapse angle of 27.0° or more is judged to have excellent tablet suitability and disintegrability.

[0154] [Difference angle (°)]: The difference angle was calculated using the formula (α) below. Difference angle = Angle of repose - Angle of collapse (α) If the difference angle is 19.0° or less, it is determined that the tablet has excellent tablet suitability and disintegrability.

[0155] [Particle size distribution (μm)]: 3 g of powder sample was measured under dry conditions using a laser diffraction particle size distribution analyzer (Mastersizer 3000 (Malvern)) and the molecular weight distribution obtained was expressed as particle size (μm) on the horizontal axis and volume (%) on the vertical axis, and the value at which the cumulative distribution is 50% was calculated. If the particle size distribution is 100 μm or more, the cohesive force between particles is improved, and it is determined that tablet suitability can be improved.

[0156] [Mortar flow (mm)]: The mortar flow of the prepared mortar was measured in accordance with the flow test of "JIS A 1171:2016 (Test method for polymer cement mortar)".

[0157] [Evaluation of powder fluidity] 1 g of the solid cement dispersant was placed on the inner wall of a stainless steel funnel (inner diameter φ10 mm). Then, while applying vibration to the funnel by hand, it was evaluated whether the solid cement dispersant passed through the funnel. The powder flowability was judged according to the following criteria based on the degree of passage of the solid cement dispersant. A: The solid cement dispersant passes through the funnel and has excellent powder flowability. B: Although the solid cement dispersant adheres to the funnel wall, it passes through the funnel and has slightly better powder fluidity. C: The solid cement dispersant does not pass through the funnel, and the powder fluidity is poor.

[0158] [Evaluation of tablet moldability (ease of compaction)]: 10 g of a sample was placed in a cylindrical mold with a diameter of 10 cm and dried in a dryer at 50°C for 30 minutes, then removed from the container and visually evaluated. 〇: It is solid and can be held △: Partially solidified ×: Not solidified, returns to powder when the mold is removed

[0159] [Disintegrability test]: 500 mL of 10-15°C water was placed in a 500 mL graduated cylinder, the tablet sample prepared in the above tablet moldability evaluation was added, and the time it took for the disintegrated sample to fall to the bottom was measured. A disintegration time of 20 seconds or less indicates excellent disintegrability.

[0160] (Production Example 1: Production of Component (A-1)) Wood (radiata pine) was digested with magnesium sulfite at 140°C for 3 hours under the condition of a solution pH of 2, and the resulting sulfite digestion waste liquid was adjusted to pH 5.0. This was subjected to ultrafiltration using a polysulfone-based ultrafiltration membrane with a molecular weight cutoff of 20,000, and the concentrated liquid was used as the lignin derivative (A-1).

[0161] (Production Example 2: Production of Component (A-2)) Wood (radiata pine) was digested with magnesium sulfite at 140°C for 3 hours under the condition of a solution pH of 2, and the resulting sulfite digestion waste liquid was adjusted to pH 12 with 40% NaOH and then oxidized with alkaline air for 30 minutes at 140°C. Insoluble matter was then centrifuged, and the supernatant was used as the lignin derivative (A-2).

[0162] (Production Example 3: Production of component (A-3)) Wood (radiata pine) was digested with calcium sulfite at 140°C for 3 hours under the condition of a solution pH of 2, and the resulting sulfite digestion waste liquor was adjusted to pH 7.0 to obtain the lignin derivative (A-3).

[0163] (Production Example 4: Preparation of component (B-1)) In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube and a dropping device, 2733 parts of water and 600 parts of an ethylene oxide adduct of methallyl alcohol (average number of moles of ethylene oxide added: 53) were charged, and the reaction vessel was replaced with nitrogen while stirring. After heating to 40°C under a nitrogen atmosphere, a monomer aqueous solution obtained by mixing 126 parts of acrylic acid, 5 parts of 3-mercaptopropionic acid and 654 parts of water, a mixed solution of 2 parts of hydrogen peroxide and 244 parts of water, and a mixed solution of 5 parts of L-ascorbic acid and 245 parts of water were continuously dropped into the reaction vessel while maintaining the temperature at 40°C for 2 hours each. After the dropping was completed, the mixture was reacted for another hour while maintaining the temperature, to obtain an aqueous solution of a copolymer. The copolymer in the liquid was copolymer (B-1) (weight average molecular weight: 22,000, Mw / Mn: 1.60).

[0164] (Production Example 5: Preparation of component (B-2)) 7900 kg of water was charged into a stainless steel reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube and a dropping device, and the reaction vessel was replaced with nitrogen under stirring. After heating to 100°C under a nitrogen atmosphere, a monomer aqueous solution containing 2503 kg (33 mol%) of methoxypolyethylene glycol methacrylate (MPEG-MA) (average number of moles of ethylene oxide added: 14), 405 kg (67 mol%) of methacrylic acid (MAA), and 2666 kg of water, 50 kg of sodium persulfate, and 500 kg of water were continuously dropped into the reaction vessel held at 100°C over 2 hours. The polymerization reaction was carried out for 1 hour while the temperature was held at 100°C. After that, the mixture was cooled to 70°C in an additional device located at the rear of the reaction vessel, neutralized to pH 6 with sodium hydroxide, and water was added at the same time to obtain an aqueous solution of copolymer with a concentration of 20%. The copolymer in the liquid was copolymer (B-2) (weight average molecular weight Mw 19,300, Mw / Mn 1.54).

[0165] (Production Example 6: Preparation of component (B-3)) 254 parts of water was charged into a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube and a dropping device, and the inside of the reaction vessel was replaced with nitrogen under stirring. After heating to 100°C under a nitrogen atmosphere, a monomer aqueous solution containing 35 parts of methacrylic acid, 214 parts of methoxypolyethylene glycol methacrylate (average number of moles of ethylene oxide added: 14), 3 parts of 3-mercaptopropionic acid and 40 parts of water, and a mixed solution containing 3 parts of ammonium persulfate and 36 parts of water were continuously dropped into the reaction vessel held at 100°C for 2 hours each. Furthermore, the reaction was carried out for 1 hour while keeping the temperature at 100°C. Thereafter, the pH was adjusted to 7 with a 31% aqueous sodium hydroxide solution to obtain an aqueous solution of the copolymer. The copolymer in the liquid was copolymer (B-3) (weight average molecular weight: 13,000, Mw / Mn: 1.41).

[0166] (Production Example 7: Preparation of component (B-4)) In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, a nitrogen inlet tube and a dropping device, 654 parts of water and 18 parts of polyethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 10) were charged, and the reaction vessel was replaced with nitrogen while stirring. After heating to 80°C under a nitrogen atmosphere, a monomer aqueous solution containing 10 parts of methacrylic acid, 0.1 parts of acrylic acid, 50 parts of methoxypolyethylene glycol methacrylate (average number of moles of ethylene oxide added: 25), 80 parts of 2-hydroxypropyl acrylate, and 142 parts of water, and a mixed solution of 3 parts of ammonium persulfate and 43 parts of water were continuously dropped into the reaction vessel held at 100°C for 2 hours each. After the dropping was completed, the mixture was reacted for another hour while maintaining the temperature at 100°C to obtain an aqueous solution of a copolymer. The pH of this liquid was adjusted to 4 with a 30% NaOH aqueous solution. The copolymer in the liquid was copolymer (B-4) (weight average molecular weight: 24,500, Mw / Mn: 2.15).

[0167] (Example 1: Production of additive for powdered hydraulic composition) The powder was prepared by drying the components (A-1) and (B-1) in the formulation shown in Table 1 at 140° C. using a drum dryer. The solid content of the powder was 95%.

[0168] (Example 2: Production of additive for powdered hydraulic composition) A mixture of component (A-2) and component (B-2) in the formulation shown in Table 1 was dried in a drum dryer at 140° C. to produce a powder. The solid content of the powder was 96%.

[0169] (Examples 3 to 5: Production of additives for powdered hydraulic compositions) The powdered products were prepared by drying the components (A-1) and (B-2) in a drum dryer at 140° C. in the formulation shown in Table 1. The solid content of the powdered product in Example 3 was 95%, the solid content of the powdered product in Example 4 was 97%, and the solid content of the powdered product in Example 5 was 97%.

[0170] (Example 6: Production of additive for powdered hydraulic composition) The powder was prepared by drying the components (A-1) and (B-3) in the formulation shown in Table 1 at 140° C. using a drum dryer. The solid content of the powder in Example 6 was 95%.

[0171] (Example 7: Production of additive for powdered hydraulic composition) The powder was prepared by drying the components (A-1) and (B-4) in the formulation shown in Table 1 at 140° C. using a drum dryer. The solid content of the powder in Example 7 was 96%.

[0172] (Comparative Example 1: Production of Additive for Powdered Hydraulic Composition) This is a powdery product obtained by drying the component (A-1) produced in Production Example 1 with a spray dryer (inlet temperature 300° C., outlet temperature 100° C.). The solid content of the powdery product was 94%.

[0173] (Comparative Example 2: Production of additive for liquid hydraulic composition) This is a liquid product produced using the component (B-3) produced in Production Example 6 as is.

[0174] (Comparative Example 3: Production of additive for liquid hydraulic composition) This is a liquid product produced using the component (B-4) produced in Production Example 7 as is.

[0175] Details of the above additives for hydraulic compositions are shown in Table 1 below.

[0176] [Table 1]

[0177] (Examples 8 to 10: Production of additives for solid hydraulic compositions) The powder was prepared by drying the components (A-1) and (B-3) in a drum dryer at 140° C. according to the formulation shown in Table 2. The solid content of the solid product of Example 8 was 97%, the solid content of the solid product of Example 9 was 98%, and the solid content of the solid product of Example 10 was 97%.

[0178] (Example 11: Production of additive for solid hydraulic composition) A mixture of component (A-1) and component (B-1) according to the formulation shown in Table 2 was dried in a drum dryer at 140° C. to produce a powder. The solid content of the powder was 97%.

[0179] (Example 12: Production of additive for solid hydraulic composition) The powder was prepared by drying the components (A-1) and (B-2) in the formulation shown in Table 2 at 140° C. using a drum dryer. The solid content of the powder was 97%.

[0180] (Example 13: Production of additive for solid hydraulic composition) The mixture of component (A-2) and component (B-2) in the formulation shown in Table 2 was dried at 140° C. in a drum dryer to give a lump. The solid content of the lump was 96%.

[0181] (Example 14: Production of additive for solid hydraulic composition) The mixture of component (A-3) and component (B-2) in the formulation shown in Table 2 was dried at 140°C using a drum dryer to produce a lump, which was then pulverized for 30 seconds using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., model: SK-M2 type). The solid content of the pulverized product was 98%.

[0182] (Example 15: Production of additive for solid hydraulic composition) A mixture of component (A-1) and component (B-3) according to the formulation shown in Table 1 was dried in a drum dryer at 140° C. to produce a powder. The solid content of the powder was 97%.

[0183] (Comparative Example 4: Additive for liquid hydraulic composition) This is a liquid product produced using the component (B-2) produced in Production Example 5 as is.

[0184] Details of the above additives for hydraulic compositions are shown in Table 2 below.

[0185] [Table 2]

[0186] Mortar was prepared and a mortar flow test was carried out for each of the additives for hydraulic compositions shown in Table 1. The conditions for preparing the mortar are shown below.

[0187] At an ambient temperature (20°C), cement, water, and sand in the proportions shown in Table 3 and additives for hydraulic compositions shown in Tables 4 and 5 were added and mechanically mixed with a mortar mixer at low speed for 60 seconds and high speed for 90 seconds to obtain mortars (hydraulic compositions) of the examples and comparative examples. The mortars were used to measure the mortar flow value. The test results are shown in Table 4.

[0188] [Table 3]

[0189] Details of the symbols in Table 3 are given below. C: Mix the following three types of cement in equal amounts: Ordinary Portland cement (manufactured by Ube Mitsubishi Cement Co., Ltd., specific gravity 3.16) Ordinary Portland cement (manufactured by Taiheiyo Cement Corporation, specific gravity 3.16) Ordinary Portland cement (Tokuyama Corporation, specific gravity 3.16) W: Tap water S: Fine aggregate (land sand from Kakegawa, density 2.58)

[0190] [Table 4]

[0191] As can be seen from Table 4, the sintered ... 3 It can be seen that if the polysaccharide has a molecular weight of 100 or less, it exhibits powder fluidity equivalent to that of a lignin derivative, and also exhibits initial dispersibility and dispersion retention superior to those of a lignin derivative. In addition, when Example 6 (using A-1 and B-3) and Comparative Example 2 (using only B-3) are compared, as well as Example 7 (using A-1 and B-4) and Comparative Example 3 (using only B-4), it is found that the powdery hydraulic composition additives of Examples 3 and 4 have superior dispersibility because the mortar flow is larger even 30 minutes after kneading than the liquid hydraulic composition additives of Comparative Examples 2 and 3. When the powdery material of Example 8 (Table 2) was subjected to a similar test with a solid content of 1.20%, the mortar flow immediately after kneading and 30 minutes after kneading was 200 mm and 190 mm, respectively, and the powder fluidity was rated B.

[0192] Mortar was prepared for the additives for hydraulic compositions shown in Table 2, and a mortar flow test was performed. The preparation conditions for the mortar were the same as those described above, except that the additives shown in Table 2 (tablets obtained by the method described in the measurement method for tablet moldability) were used instead of the additives shown in Table 1. The test results are shown in Table 5.

[0193] [Table 5]

[0194] As can be seen from Table 5, all of Examples 8 to 14 were excellent in terms of tablet moldability and disintegrability in a well-balanced manner. From this, it can be seen that if the composition contains at least a lignin derivative and a copolymer composed of a predetermined structural unit, has a disintegration angle of 27.0° or less, and has a particle size distribution of 100 μm or more, it is easy to solidify and the obtained solidified product has good solubility in the hydraulic composition. Furthermore, when Example 10 (using A-1 and B-3) is compared with Comparative Example 2 (using only B-3), and Example 12 (using A-1 and B-2) is compared with Comparative Example 4 (using only B-2), the solid hydraulic composition additives of Examples 10 and 12 have the same or greater mortar flow immediately after mixing and after 30 minutes than the liquid hydraulic composition additives of Comparative Examples 2 and 4, and therefore are found to have dispersibility equal to or greater than that of the liquid hydraulic composition additives of Comparative Examples 2 and 4. Furthermore, it is understood that, although Example 13 is a lump, the mortar flow performance is excellent like Examples 8 to 12 and 14. Example 15 has good dispersibility and is predicted to obtain a good evaluation (eg, B or higher) in the powder fluidity test.

Claims

1. Component (A): a lignin derivative, and Component (B): A copolymer having at least two kinds of structural units selected from the group consisting of a structural unit (I) derived from a monomer represented by the following general formula (1), a structural unit (II) derived from a monomer represented by the following general formula (2), and a structural unit (III) derived from a monomer represented by the following general formula (3), The repose angle is 50.0° or less, and the loose bulk density is 0.40 g / cm 3 A powdery composition that satisfies at least one of the following: a collapse angle of 27.0° or more; and a particle size distribution of 100 μm or more. 【Chemistry 1】 (In the general formula (1), R 1 ~R 3 Each of A and B independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. p represents an integer of 0 to 2. q represents an integer of 0 to 1. 1 O may be the same or different and represents an oxyalkylene group having 2 to 18 carbon atoms. n represents an integer of 1 to 300. 4 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. 【Chemistry 2】 (In the above general formula (2), R 5 ~R 7 each independently represents a hydrogen atom, a methyl group, or -(CH 2 ) r COOM 2 Here, -(CH 2 ) r COOM 2 When it represents a group, -COOM 1 group or other -(CH 2 ) r COOM 2 When an anhydride group is formed, the M 1 Or M 2 does not exist. 1 ~M 2 each independently represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group; and r represents an integer of 0 to 2. 【Chemistry 3】 (In the general formula (3), R 8 ~R 10 R each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 11 represents a hydrocarbon group having 1 to 4 carbon atoms which may contain a heteroatom; and s represents an integer of 0 to 2.

2. The composition of claim 1 , wherein the collapse angle is 30.0° or greater.

3. The composition according to claim 1 or 2, wherein the difference angle represented by the following mathematical formula (α) is 19.0° or less. Difference angle = Angle of repose - Angle of collapse (α)

4. The angle of repose is 50.0° or less, and the loose bulk density is 0.40 g / cm 3 The composition according to any one of claims 1 to 3, wherein:

5. 5. The composition of claim 4, wherein the weight ratio of component (A) to component (B) ((A) / (B)) is from 99:1 to 51:

49.

6. The composition according to any one of claims 1 to 3, having a collapse angle of 27.0° or more and a particle size distribution of 100 μm or more.

7. 7. The composition of claim 6, wherein the weight ratio of component (A) to component (B) ((A) / (B)) is from 50:50 to 1:

99.

8. A solid composition which is a solidified product of the composition according to any one of claims 1 to 7.

9. The composition according to claim 8, which is a solidified product of the composition according to claim 6 or 7.

10. An additive for hydraulic compositions, comprising the composition according to any one of claims 1 to 9 as an active ingredient.

11. A hydraulic composition comprising the additive according to claim 10.

Citation Information

Patent Citations

  • Composite cement dispersant

    JP2003277114A

  • Method for producing powdery cement dispersing agent

    JP2005272216A

  • Powdery cement dispersant

    JP2008208016A

  • Cement dispersing agent, concrete admixture and cement composition

    JP2009242197A

  • Dispersant

    JP2011240224A